Cardiovascular Risk According to Plasma Apolipoprotein and Lipid Profiles in a Canadian First Nation**This article is part of a joint publication initiative between Preventing Chronic Disease and Chronic Diseases in Canada. Preventing Chronic Disease is the primary publisher, while Chronic Diseases in Canada is the secondary publisher. - Riediger, Natalie D.; Bruce, Sharon G.; Kue Young, T.
Introduction Despite high diabetes rates among Canadian First Nations people, little is known about their cardiovascular disease risk. Our aim was to describe the apolipoprotein profile with respect to cardiovascular risk in a Canadian First Nation community. Methods In 2003, a representative sample of adult members of a Manitoba First Nation (N = 483) participated in a screening study for diabetes and diabetes complications. We assessed their cardiovascular risk factors. Results Sixty percent of women were at increased cardiovascular risk because of low apolipoprotein A1 (apoA1) levels, compared with 35% of men. The proportion of women with low apoA1 levels decreased with age, but the proportion with low high-density lipoprotein levels remained stable across age groups. Both apoB and apoA1 were significantly associated with obesity when age, sex, diastolic blood pressure, homocysteine, diabetes, and insulin resistance were controlled for. Conclusion Apolipoprotein and lipid profiles in this First Nation population suggest high cardiovascular risk. Future research should characterize the lipoprotein particle size in this population.